The Romance of Heroism and Heroic Leadership - Goethals, George R.; Allison, Scott T. (Emerald, 2019)
Heroes permeate our culture. But what makes a hero? And what makes heroes 'heroic'? This exciting and innovative study explores how charisma and human needs create images of individuals as heroes and villains.